Towards a collaborative governance regime for disaster risk reduction: Exploring scalar narratives of institutional change in Nepal. (September 2021) - Russell, Caroline; Clark, Julian; Hannah, David; Sugden, Fraser
Abstract: This paper contributes to the study of collaborative governance (CG) - systems where autonomous actors work together around shared objectives using pooled resources to address a common goal. Among CG's claimed benefits are boosting actor capacities for transformative action and increasing their resilience to complex multi-scaled challenges such as hazards and sudden catastrophic events. We engage with collaborative governance through a case study of changing public policy and institutional structures that govern hazards in Nepal. Following the shocking event of the 2015 Gorkha earthquake, Nepal's approach to disaster risk reduction (DRR) has been reshaped by federalisation and institutional reforms that aim to embed a governing system based on greater collaboration. We argue this amounts to a state transition to a collaborative governance regime (CGR) for DRR. Using primary qualitative data derived from 17 semi-structured interviews at national, provincial, and local scales, we identify state-sponsored scalar narratives around 1) actor capacities and tendencies in DRR; 2) knowledge production on DRR and its dissemination; and 3) formal and informal institutional DRR roles and responsibilities. We show how these narratives are being used as anchor points for a new CG approach to national DRR strategy. However, our analysis shows these narratives risk excluding local participation in DRR by marginalising grassroots politics to emphasise top-down state-led goals. In turn, this leads us to question the viability of the emerging governance regime as a truly collaborative project embedding principles of sustainability and inclusivity. We conclude that if these state scalar narratives continue to shape national policy, they will impede the potential for transformative collaborative action for DRR in Nepal. Highlights: Looks at the use of the discourse of collaborative governance. Case study of institutional changes to Nepali DRR after the 2015 earthquake. Identifies state scalar narratives for collaborative governance regime. Finds that collaborative governance regime is not truly collaborative. Current trajectory risks ignoring local level politics and needs.